Canada's changing innovation landscape. (8th September 2021) - Alam, Md. Razib; Koo, Bonwoo; Cozzarin, Brian Paul
Abstract: Our objective is to study Canada's patenting activity over time in aggregate terms by destination country, by assignee and destination country, and by diversification by country of destination. We collect bibliographic patent data from the Canadian Intellectual Property Office and the United States Patent and Trademark Office. We identify 19, 957 matched Canada–US patents, 34, 032 Canada-only patents, and 43, 656 US-only patents from 1980 to 2014. Telecommunications dominates in terms of International Patent Classification technologies for US-only and Canada–US patents. At the firm level, the greatest number of matched Canada–US patents were granted in the field of telecommunications, at the university level in pharmaceuticals, at the government level in control and instrumentation technology, and at the individual level in civil engineering. We use entropy to quantify technological diversification and find that diversification indices decline over time for Canada and the USA; however, all US indices decline at a faster rate.